Impact of the COVID-19 pandemic on emergent pacemaker implantation during lockdown and its aftermath. (14th October 2021) - De Almeida Fernandes, D; Cadete, R; Guimaraes, J; Monteiro, E; Costa, G; Antonio, N; Goncalves, L
Abstract: Background: COVID-19 was first considered a pandemic on the 11th of March of 2020 by the World Health Organization. Its impact comprised not only the direct consequences of the disease but a decrease in the follow-up and interventions of patients with cardiovascular (CV) disease. In Portugal and the World, the consequences of this complex paradigm shift on emergent pacemaker implantation rates during and after this pandemic is largely unknown. Purpose: We sought to analyse the impact of COVID-19 pandemic on emergent pacemaker implantation rate and patient profile in a tertiary hospital during the first Portuguese lockdown and subsequent post-lockdown period. Methods: We retrospectively reviewed the clinical profile of patients who had pacemakers implanted in our hospital in an urgent/emergent setting from March 18, 2020 to May 17, 2020 (lockdown) and May 19 to July 17, 2020 (post-lockdown). This data was then directly compared to the homologous periods from the year before (H1 and H2, respectively). Results: A total of 180 patients submitted to emergent pacemaker implantation were included. The cohort was comprised of 29 patients who had a pacemaker implanted during lockdown, 60 post-lockdown, 38 in H1 (+31% vs lockdown) and 53 in H2. Average age and gender proportion were similar for all groups. When comparing lockdown and post-lockdown periods, the number of cases significantly increased in the second period (+106.9%) and there was a tendency for a higher number of temporary pacemaker use (3.4% vs 16.7%; p=0.076). Patients admitted during lockdown were 7.57 times more likely to present with hypotension/shock (odds ratio (OR) 7.57; p=0.013). Regarding lockdown and its homologous 2019 period, there was a decrease in the number of patients admitted (−23.7%). Again, there was a higher tendency for hypotension on presentation during lockdown (p=0.054). In comparison to its homologous 2019 period, post-lockdown saw a slight increase in the number of patients (+13.2%) and more patients presented with bradycardia (16.7% vs 3.8%; p=0.026). Also of note, no patients were admitted to the emergency department during lockdown for anomalies detected on ambulatory tests (Holter, electrocardiogram or implanted loop recorder). Conclusion: During lockdown, clinical presentation was generally more severe, with a greater number of patients presenting with hypotension/shock. In addition, there appears to be a lockdown effect on emergent bradyarrhtmias admissions in the post-lockdown period with a profound impact: higher admission rates and more severe presentations including a higher need of temporary pacemaker. Patients with symptoms suggestive of bradyarrhythmias should be advised to present promptly regardless of the pandemic. Funding Acknowledgement: Type of funding sources: None.